Pengaruh Kompetensi Aparatur Pengelola Dana Desa, Sistem Pengendalian Internal, Dan Pemanfaatan Teknologi Informasi Terhadap Akuntabilitas Pengelolaan Dana Desa (Studi Kasus Pada Desa Yang Berada Di Kabupaten Tasikmalaya) - Sri Rahayu; Dewi Fatimah Kartawinagara (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this analysis was to determine the influence of the competency of village fund management officers, internal control procedures were working to manage monetary resources in small communities, and the incorporation of IT contributes to making village financial administration accountable. This study used a non-probability sampling strategy, namely in all village apparatus in Tasikmalaya Regency, West Java, a total of 351 villages. Multiple linear regression was performed statistically using SPSS version 25. Discussion of these findings data reveals that the responsibility for managing village funds in Tasikmalaya Regency is expected to increase dramatically in 2022, influenced by the competency of village fund management officers, internan control system, and IT utilization.